Add the following: (5x2 + x + 7) + (3x2 - 4x + 3)

Question

Asked 10/1/2010 4:59:59 PM

Updated 6/26/2014 6:22:30 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by alfred123 [6/26/2014 6:22:28 PM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Expert answered|Mitchell|Points 4133|

Question

Asked 10/1/2010 4:59:59 PM

Updated 6/26/2014 6:22:30 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by alfred123 [6/26/2014 6:22:28 PM]

Rating

8

(5x^2 + x + 7) + (3x^2 - 4x + 3)

= 5x^2 + 3x^2 + x - 4x + 7 + 3;

= 8x^2 - 3x + 10

= 5x^2 + 3x^2 + x - 4x + 7 + 3;

= 8x^2 - 3x + 10

Added 6/26/2014 6:22:30 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/26/2014 10:00:16 PM]

Solve:11b - 6 = 10b + 4 **Weegy:** 11b - 6 = 10b + 4;
11b - 10b = 4 + 6;
b = 10 (More)

Question

Expert Answered

Updated 4/13/2014 8:35:19 AM

1 Answer/Comment

Solve: z - 6.68 = 7.47

Question

Updated 4/13/2014 8:34:42 AM

2 Answers/Comments

z - 6.68 = 7.47;

z = 7.47 + 6.68;

z = 14.15

z = 7.47 + 6.68;

z = 14.15

Added 4/13/2014 8:34:42 AM

This answer has been confirmed as correct and helpful.

Simplify: 10x - 2 + 3x **Weegy:**
10x - 2 + 3x = 13x - 2
(More)

Question

Expert Answered

Updated 12/1/2014 6:24:23 AM

0 Answers/Comments

Simplify: 10x - 2 + 3x

Question

Updated 4/30/2014 4:07:54 PM

2 Answers/Comments

10x - 2 + 3x = 13x -2

9(a+8) - 5(a-10) = 9a + 72 - 5a + 50 = 4a + 122

Note: Multiplication of the same sign is positive (+).

9(a+8) - 5(a-10) = 9a + 72 - 5a + 50 = 4a + 122

Note: Multiplication of the same sign is positive (+).

Added 9/26/2010 3:00:30 PM

9(a + 8) - 5 (a - 10);

9a + 72 - 5a + 50

= 4a + 122

9a + 72 - 5a + 50

= 4a + 122

Added 4/30/2014 4:07:54 PM

This answer has been confirmed as correct and helpful.

Multiply:(5x + 1)(2x - 2) **Weegy:** 10x -10x +2x -2 = 2x -2 (More)

Question

Expert Answered

Updated 12/1/2014 6:13:31 AM

1 Answer/Comment

(5x + 1)(2x - 2)

= 10x^2 - 10x + 2x - 2;

= 10x^2 - 8x - 2

= 10x^2 - 10x + 2x - 2;

= 10x^2 - 8x - 2

Added 12/1/2014 6:13:31 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [12/1/2014 6:23:50 AM]

38,924,114

questions answered

There are no comments.